Local food ingredients of purple sweet potato MP ASI prevent stunting: quasi-experimental study - Noya, Fransisca; SKM.M.Kes, Mercy; Tempali, S.Kep.,Ns.,M.Sc, Sri (Public Health of Indonesia, 2025)
Background:Purple sweet potato is a locally abundant ingredient in Banggai Regency, Central Sulawesi Province. However, many individuals, particularly mothers of toddlers, remain unaware of the nutritional benefits and the methods for processing sweet potatoes into complementary foods for breastfed infants. Objective:This study aims to examine the effect of assistance in preparing complementary foods (MP ASI) using locally sourced purple sweet potatoes on the incidence of stunting. Method:This research employs a quasi-experimental design with a pre-experimental one-group pretest-posttest approach. The study involved 38 mothers of infants aged 7–12 months, selected through purposive sampling. Data were collected using a validated questionnaire and analyzed using univariate and bivariate statistical methods. Results:The findings reveal a significant relationship between the introduction of complementary feeding (IMD) and exclusive breastfeeding on the incidence of stunting, with a p-value <0.05 (0.000). Additionally, there was a notable improvement in maternal knowledge and skills related to complementary feeding before and after the intervention (p < 0.05). The use of purple sweet potato as MP ASI was found to contribute to a reduction in the incidence of stunting (100%). Conclusion:The education and training provided on complementary feeding using locally available food ingredients, such as purple sweet potatoes, significantly enhanced the knowledge and skills of mothers with infants aged 7–12 months and effectively reduced the incidence of stunting.  Keywords:mentoring; purple sweet potato; knowledge; skills; MP ASI; stunting